Pengaruh Manajemen Laba, Intensitas Modal dan Transfer Pricing terhadap Penghindaran Pajak: (Studi Empiris pada Perusahaan Sektor Energi yang Terdaftar di Bursa Efek Indonesia Tahun 2019 - 2023) - Fany Maulida, (Jurnal Mahasiswa Manajemen dan Akuntansi, 2025)
Tax avoidance is a major issue in the corporate sector, impacting state revenue and fairness in tax distribution. This study analyzes the effects of Earnings Management, Capital Intensity, and Transfer Pricing on Tax Avoidance in energy sector companies listed on the Indonesia Stock Exchange (IDX). Using a quantitative approach, the research relies on secondary data from company financial statements. The population includes all energy sector companies listed on the IDX for 2019–2023. Through purposive sampling, 12 companies were selected, producing 60 observations over five years. Panel data regression with Eviews 12 was applied to test the hypotheses. Results show that simultaneously, Earnings Management, Capital Intensity, and Transfer Pricing significantly influence Tax Avoidance. Partially, Earnings Management has a positive significant effect, meaning companies engaging in earnings management tend to avoid taxes. Capital Intensity shows no significant effect, indicating that investment levels in fixed assets do not affect tax avoidance practices. Transfer Pricing also has no significant effect, possibly due to strict regulations or specific operational traits of the energy sector. The study offers both theoretical insights and practical implications for understanding factors driving tax avoidance in Indonesia’s energy industry.